Open Data for Territorial Specialization Assessment Territorial Specialization in Attracting Local Development Funds: an Assessment. Procedure Based on Open Data and Open Tools - Las Casas, Giuseppe; Lombardo, Silvana; Murgante, Beniamino; Pontrandolfi, Piergiuseppe; Scorza, Francesco (TeMA - Journal of Land Use, Mobility and Environment, 2014)
The New Cohesion Policy opens to an integrated place-based approach for the improvement of territorial and social cohesion. The issue of territorial impact assessment of regional development policies highlight that data availability, open access to datasets in “near real-time”, participation, knowledge sharing, assumed importance within the development planning process. The contribution of ‘open data’ appears to be mature and in this paper we present an application of spatial analysis techniques for the evaluation of spatial effects of EU funds starting form open data by open-coesione. The application regards an internal areas of Basilicata Region: the Agri Valley. A complex contests in which an environmental and agricultural traditional vocation conflicts with a recent development of oil extraction industries. Conclusions regard further applications and perspectives for improving and supporting regional development planning considering the exploitation of open data sources and spatial analysis.